Nonlinear magnetohydrodynamics of pulsed parallel current drive in reversed-field pinches - Reynolds, J. M.; Sovinec, C. R.; Prager, S. C. (Physics of plasmas, 2008)
Nonlinear simulation with a simple resistive magnetohydrodynamics model is used to investigate the stabilization of magnetic fluctuations in reversed-field pinch plasmas subject to pulsed-parallel current drive. Numerical results are diagnosed with computations of nonlinear power transfer and by evaluating sequences of profiles for linear stability. Results show that poloidal electric field pulsing promptly affects the exchange of energy between the mean profiles and both core-resonant m = 1 fluctuations and high-axial-wavenumber fluctuations. Linear computations show that slight changes in edge profiles are sufficient to alter the stability of the marginal state. There is a slight delay in the response of energy exchanged among fluctuations, which reduces the m = 0 fluctuations. Loss of dynamo effect as fluctuation amplitudes decrease leads to nonlocal pulse penetration that enhances pinching when toroidal drive is maintained. Reducing toroidal drive together with the application of poloidal electric field avoids pinching and maintains the stabilizing effect for a greater period of time.